Point-Counterpoint: Piperacillin-Tazobactam Should Be Used To Treat Infections with Extended-Spectrum-Beta-Lactamase-Positive Organisms - Schuetz, Audrey N. (J Clin Microbiol, 2018)
Beta-lactam/beta-lactamase inhibitor combination antimicrobials (BLBLIs) are among the most controversial classes of antibiotic agents available for the treatment of infections caused by extended-spectrum-beta-lactamase (ESBL)-producing Gram-negative bacteria (ESBL-GNR). Piperacillin-tazobactam (PTZ) is one of the most frequently utilized antibiotic agents for empirical Gram-negative bacterial coverage and remains active against a large proportion of ESBL-GNR strains. Furthermore, good antimicrobial stewardship practices encourage the use of carbapenem-sparing treatment regimens for infections due to ESBL-GNR. As rapid diagnostics are increasingly used in the clinical microbiology laboratory and have the capability of detecting CTX-M type or other ESBL resistance mechanisms, this issue continues to be pertinent. Some data imply reduced efficacy of PTZ against ESBLs. Several factors may affect a clinician's choice to use BLBLIs, including the isolate's MIC, the site and severity of infection, and the type of resistance mechanism. These factors are explored in this review of the pros and cons of BLBLI treatment of invasive infections due to ESBL-producing bacteria, as well as how laboratories should report results for BLBLIs for these organisms as they relate to antimicrobial stewardship. In this Point-Counterpoint, Audrey Schuetz provides the pro point of view and Sergio Reyes and Pranita Tamma provide the con, counterpoint view.